Omed-Omedan as a Traditional Cultural Expression: Legal Protection of a Communal Intellectual Property in Indonesia - Dwijayanthi, Putri Triari; Samsithawrati, Putu Aras; Sawitri, Dewa Ayu Dian (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 11 No 4 (2022), 2022)
The study was aimed to identify, analyze and elaborate the legal arrangement for communal intellectual property protection in Indonesia, including “omed-omedan”. Further, the study also examined the commercial use mechanism of Traditional Cultural Expression, including “omed-omedan”. This writing was normative legal research using statutory approach and conceptual approach. The study indicates that omed-omedan shall be protected as TCE, hence any commercial use of omed-omedan by major industries and/or foreign investors must obtain a permit and fulfill other obligations including but not limited to the distribution of benefits to customary law community in Banjar Kaja, Sesetan as the custodian.